Sustainable Post-War Recovery of Ukraine’s Regions and Green Economy: Challenges and Opportunities Amidst the Environmental Impacts of Military Actions - Karaim, Olha (Харківський національний педагогічний університет імені Г.С. Сковороди, 2024)
The full-scale military invasion of Ukraine in 2022 has led to widespread destruction of infrastructure, industrial facilities, and devastation of natural resources. Beyond the humanitarian catastrophe, the war has posed unprecedented challenges to environmental security and sustainable development. Amid the urgent need for rapid national recovery, the question arises of integrating green economy principles and sustainable development into the reconstruction process, which will help mitigate negative environmental impacts and ensure long-term economic resilience. The article explores the integration of sustainable post-war recovery concepts and a green economy for Ukraine, based on current data on the environmental damage caused by the war. It analyzes the opportunities for implementing environmental initiatives during the country’s reconstruction process.
Keywords: Sustainable development; green economy; environmental impacts of military actions